Optimization of Formula and Physicochemical Characterization of Noodles Based on Modified Cassava Flour with Addition of Soybean Flour and Skim Milk - Santi Dwi Astuti; Laksmi Putri Ayuningtyas; Indah Fitri Haryani (Indonesian Journal of Food Technology, 2023)
Noodles are a popular food and are usually made from wheat flour, this causes the level of dependence on wheat flour increase. In previous research, an alternative to the use of modified cassava flour as a substitute for wheat flour has been found and a good product has been obtained, but the product has the disadvantage of low protein content. So that in this study, modifications were made by adding soy flour and skim milk to increase protein levels in mocaf noodles. This research aims to set the proportion of soy flour and skim milk in producing noodles with modified cassava. The other aim is to examine te effect of the proportion of mocaf flour : soy flour and skim milk on the characteristic of the physicochemical and sensory properties of the noodles produced; and comparing physicochemical and sensory characteristics between noodles products using optimum formula, and control (100% wheat flour). This research uses the Response Surface Methodology (RSM) with an experimental design using Central Composite Design (CCD). The results of this research are the optimum formula of mocaf dried noodles with the addition of soy flour and skim milk with the highest desirability at 0.786 in the soy flour formula at 8.02%, and skim milk 17.07%. The sensory test results of mocaf dried noodles show that an increase in the proportion of soy flour causes an increase in color response, beany flavor, cooking loss, and rehydration time, as well as causing a decrease in chewiness, cassava flavor, milky flavor, elasticity, preference, and elongation. Increasing the concentration of skim milk causes an increase in chewiness, color, milky flavor, elasticity, preference, cooking loss, and rehydration time and causes a decrease in cassava flavor, beany flavor, and elongation. The average results of the optimum product chemical test have a higher difference in values, including fat content of 1.12%, ash content at 1.22%, and carbohydrates of 5.22%. Meanwhile, water content and protein content have a lower value difference, i.e., the water content of 0.26% and protein content of 7.29%.